Unearthing the reality of ‘Zombie energy systems’ in Africa’s energy transition - Michael O Dioha; Magnus C Abraham-Dukuma; Prudence Dato (Environmental Research: Energy)
Africa’s energy transition is unique and complicated by—among other things—the pervasive presence of ‘Zombie Energy Systems’ (ZES). These are outdated, inefficient, and environmentally harmful energy systems that persist despite being obsolete (e.g. old and mismanaged electrical grid systems and obsolete electrical appliances). These ZES hinder Africa’s energy transition, yet they receive limited attention in the international energy development arena. Rooted in colonial-era legacies, economic constraints, and policy shortcomings, these energy systems have led to a persistent misalignment between energy supply and development goals, perpetuating energy poverty and limiting economic growth. In this piece, we identify ZES as a critical barrier to Africa’s energy transition, arguing that addressing it requires more than just infrastructure replacement. A holistic approach is needed—one that includes decommissioning outdated assets, modernizing grids, promoting energy efficiency, improving regulatory environment and fostering local expertise in modern energy systems. We advocate for a comprehensive reevaluation of energy policies and investment strategies across Africa, emphasizing the importance of balancing the development of new energy systems with the critical need to upgrade and enhance existing inefficient energy systems. Neglecting the improvement of current energy systems risks undermining the effectiveness of Africa’s energy transition. Furthermore, we highlight the necessity of implementing tailored solutions that address the distinctive energy challenges faced by each country on the continent.